The Role of Green Human Resource Management in Advancing Sustainable Development in Health Sector Institutions - Reham Ershaid Nusair, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
Sustainable development is the most important point of transformation that is seeking to be achieved at present, which requires a review of the policies and practices that govern it. Green human resource management works to stimulate environmental initiatives and increase its employees, promotes their commitment to the issue of sustainable development; the current research has come to highlight the role of applying green human resources management in achieving sustainable development in health sector institutions. The analytical descriptive approach for the research related data extracted from several sources of reading assisted the researcher in developing the results showing ideas for the research. One of the most prominent conclusions reached in the implementation of green human resources management could make great progress towards sustainable development in health sector institutions and improves the quality of health services provided and the environment to the future generations.